Analisis Pengaruh Indeks Pembangunan Manusia, Pertumbuhan Ekonomi dan Upah Minimum terhadap Tingkat Pengangguran Terbuka di Indonesia - Lina Marliana (Ekonomis: Journal of Economics and Business, 2022)
Indonesia has the largest population in Southeast Asia and is a big capital for the Indonesian nation in development. A large population, if not managed properly, will cause unemployment problems. Thus, it is necessary to research the factors that affect the open unemployment rate. This study aims to analyze the effect of the human development index, economic growth, and the minimum wage on the open unemployment rate in Indonesia. The research method used was multiple linear regression with time-series data from 2006 to 2020 and used SPSS 16.0. based on the results of multiple linear regression, namely the calculated F test, simultaneously the human development index, economic growth, and the minimum wage together have a negative and significant effect on the open unemployment rate in Indonesia. Meanwhile, the human development index has no significant effect on the open unemployment rate based on the partial T-test. Economic growth and the minimum wage significantly affect the open unemployment rate.